Total Nasal Reconstruction with a Nonlaminated Vascularized Free Temporal Fascia as the Lining. Issue 12 (December 2019) - Akita, Shinsuke; Yamaji, Yoshihisa; Yamasaki, Kazuki; Kosaka, Kentaro; Tezuka, Takafumi; Kubota, Yoshitaka; Mitsukawa, Nobuyuki
Abstract : Summary: Various methods to generate the lining for a full-thickness nasal reconstruction have been reported. We used bilateral septal mucoperichondrial flaps, the distal portion of an expanded median forehead flap, and a nonlaminated vascularized free temporal fascia flap as a lining during total nasal reconstruction of a total full-thickness nasal defect in a 45-year-old woman with a nasal squamous cell carcinoma. In the first step of the two-stage surgery, a tissue expander was inserted into the forehead simultaneously with tumor resection. In the second step, the expanded median forehead flap, cartilage graft, bilateral septal mucoperichondrial flaps, and short pedicle vascularized free temporal fascia transfer were performed. Total nasal reconstruction could be completed without any skin graft or skin paddle of the free flap. Epithelialization of the mucosa on the transferred vascularized free temporal fascia without contracture deformity of the nasal cavity was confirmed by endoscopic examination after 8 years of follow-up. In the surgical procedure described, the facial skin, including the lining of the nostril rim, and the mucous membrane of the nasal cavity were reconstructed using facial skin and mucous membrane without long-term contracture, respectively.